A simple, rapid and scalable synthesis approach for ultra-small size transition metal selenides with efficient water oxidation performance. Issue 43 (25th October 2021) - Shi, Yue; Zhang, Dan; Miao, Hongfu; Zhang, Wen; Wu, Xueke; Wang, Zuochao; Li, Hongdong; Zhan, Tianrong; Chen, Xilei; Lai, Jianping; Wang, Lei
Abstract : A simple, rapid and scalable microwave method for preparing ultra-small size transition metal selenides to boost water oxidation. Abstract : Transition metal-based nanomaterials are regarded as promising catalysts due to their low cost and abundant reserves. In particular, transition metal-based selenides exhibit excellent capability for the oxygen evolution reaction (OER). However, the currently reported synthesis approaches for transition metal-based compounds involve generally complicated, time consuming, energy-intensive and low-yield steps. Herein, we reported a simple, rapid and scalable microwave method for the first time and successfully synthesized a series of ultra-small size transition metal selenide nanoparticles (∼5 nm in diameter) loaded on the carbon nanotube (CNT) surface. The entire reaction only takes 120 seconds and enables to obtain gram-level products. By benchmarking the OER activity, the ratio and composition optimized Ni0.27 Co0.28 Fe0.30 Se@CNT exhibits superior water oxidation performance, requiring only 291 mV overpotential to achieve a current density of 100 mA cm −2 (48 mV smaller than that of the commercial RuO2, which is currently one of the most efficient transition metal-based catalysts). In addition, Ni0.27 Co0.28 Fe0.30 Se@CNT demonstrates excellent stability up to 50 hours. This work offers a highly efficient synthesis method for ultra-small size transition metal-based selenides with outstanding catalytic performance. More profoundly, this method also pioneers a creative synthesis avenue for other transition metal compounds, such as sulfides, phosphides, etc.